TOXIC NORMAL HYDROCARBONS (NHs) IN THE FISH SAMPLES FROM DIFFERENT PARTS OF BANGLADESH - M. Amzad Hossain; S. M. Salehuddin (Universitas Gadjah Mada, 2008)
Toxic normal hydrocarbon (NH), nonadecane in the dichloromethane-hexane crude extract of the flesh of fish samples collected from the different districts of Bangladesh was analyzed by GC-MS/MS. It was observed that NH deposition on the samples takes place in different morphological parts of the biological materials. The NH, nonadecane, was found in the fish samples collected from the roadside by the extraction of dichloromethane-hexane mixture solvents.